2008
DOI: 10.1007/s10764-008-9260-y
|View full text |Cite
|
Sign up to set email alerts
|

Benefits to Female Helpers in Wild Rhinopithecus roxellana

Abstract: To assess what female Sichuan snub-nosed monkeys (Rhinopithecus roxellana) gain from allowing others to care for their infants, we collected behavioral data on 12 mother-infant dyads at Zhouzhi National Nature Reserve in the Qinling Mountains, China. Mothers' feeding time significantly increased when infants were cared for by other group members versus when they were cared for by the mothers themselves. The time mothers spent autogrooming and receiving grooming also increased when they were temporarily relieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Although allomothering is a prominent feature of R . roxellana [Xi et al, 2008] and many other colobine species [Maestripieri, 1994], in the present study, there was no positive relationship between group size and female reproductive success such as was proposed by Clutton-Brock et al [2001]. This result is consistent with some reports for other social mammals [e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Although allomothering is a prominent feature of R . roxellana [Xi et al, 2008] and many other colobine species [Maestripieri, 1994], in the present study, there was no positive relationship between group size and female reproductive success such as was proposed by Clutton-Brock et al [2001]. This result is consistent with some reports for other social mammals [e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Strong relationships within OMUs may secure cohesion in the midst of a crowded neighborhood, which is particularly useful if coalitions help combat infanticidal males 69 or provide benefit through alloparental care. 46 We believe that weak within-group feeding competition and strong conspecific threat are primary factors in the social organization of snub-nosed monkeys. We nonetheless recognize that phylogeny plays a role in social systems.…”
Section: Conspecific Threat and Phylogenymentioning
confidence: 99%
“…Alloparental care, which may be another indication of femalefemale affinity, occurs regularly among both golden snub-nosed monkeys and black snub-nosed monkeys. 9,46 Few studies of snub-nosed monkeys have used individually identified animals and therefore it is difficult to document alloparental care. While alloparental care has yet to be reported for Tonkin snubnosed monkeys and gray snubnosed monkeys, further study may well reveal that this behavior is common in these two species, too.…”
Section: One-male Unitsmentioning
confidence: 99%
“…Mothers are the principle caretaker of their infants. However, individuals in the same OMU other than the mother have been observed to carry, groom, and even nurse a newborn infant in snub-nosed monkeys (Xi et al 2008).…”
Section: Introductionmentioning
confidence: 99%